2010
DOI: 10.1016/j.rmed.2009.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and airway inflammation and the presence of emphysema in patients with COPD

Abstract: The aim of this study was to determine the impact of HRCT-confirmed emphysema on biomarkers evaluating airway and systemic inflammation in COPD patients. Forty-nine consecutive male COPD outpatients with stable COPD were divided in two groups according to the presence or absence of emphysema on HRCT. Patients underwent pulmonary function tests, plus assessment of exercise capacity, body composition and quality of life. Biomarkers were measured in serum (CRP, interleukin-6, TNF-alpha, leptin, adiponectin, osteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 50 publications
5
40
0
6
Order By: Relevance
“…However, this effect was not independent of the severity of emphysema. In the present study, patients with COPD with mild to moderate disease and mild emphysema have a heterogeneous physiologic and clinical presentation of the disease according to their distribution as shown Papaioannou et al 26 found that patients with CT scandetected emphysema have higher levels of systemic oxidative stress and plasma fi brinogen.…”
Section: Discussionsupporting
confidence: 49%
“…However, this effect was not independent of the severity of emphysema. In the present study, patients with COPD with mild to moderate disease and mild emphysema have a heterogeneous physiologic and clinical presentation of the disease according to their distribution as shown Papaioannou et al 26 found that patients with CT scandetected emphysema have higher levels of systemic oxidative stress and plasma fi brinogen.…”
Section: Discussionsupporting
confidence: 49%
“…Results agree with those of Dorneles et al [28] who could not verify a difference between groups with different degrees of COPD after 6MWT, and with the data presented by Papaioannou et al [31] that did not reveal differences regarding the blood level of this biomarker in stable COPD individuals and healthy controls. However, other studies, with more consistence methodology, perceived this difference [2,32].…”
Section: Discussionsupporting
confidence: 91%
“…31 The accomplishment of 6MWT did not cause significant alteration of IL6, Hs-CRP and TNF-α (p>0.05) in COPD group. Only the control group presented a significant increase of IL-6.…”
Section: Resultsmentioning
confidence: 80%
“…También se ha observado que los valores de PCRus son más altos cuando existe compromiso extrapulmonar, ya sea por pérdida de la masa muscular periférica o por reducción de la capacidad de ejercicio 13 . Otros índices que refl ejan la gravedad de la enfermedad, como la magnitud del enfi sema, el compromiso de la masa muscular de extremidades inferiores y las alteraciones de la composición corporal, han sido escasamente evaluados 14,15 . Por otro lado, los niveles de PCRus son mayores en los pacientes con EPOC que presentan comorbilidades asociadas, como la enfermedad cardiovascular aterosclerótica (ECA) 16 ; caquexia 17 , obesidad 18 ; y cáncer pulmonar 19 , entre otras 20,21 .…”
unclassified